If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 = 27 Reorder the terms: -4 + 4x = 27 Solving -4 + 4x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4x = 27 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 27 + 4 4x = 27 + 4 Combine like terms: 27 + 4 = 31 4x = 31 Divide each side by '4'. x = 7.75 Simplifying x = 7.75
| 0.15x+0.6(x-2)=0.01(3x-5) | | 5(-5)-2(2)= | | 11t/28-t/4=1 | | x-2(3x-2)=-6+4x-8 | | -15*x=2 | | g(-x)=x^2+10x+35 | | 5-4(3m-6)=5 | | 4(3+1.25)+5y=12.00 | | 6y+3-8=-37 | | 5x+6x-(3x+5)= | | V+9=1 | | x^3-6x+9x=0 | | 6n+4+2=-24 | | -10-5(1+j)= | | -2x+1=-2(x+5) | | 6x-8+8=6 | | 3(-9h+10)= | | 13/1/3 | | 3(x^2-1)=24 | | 5(-7g-2)= | | 5/2(n-92) | | x/7-x/5=1/7 | | -68+5x+x=64 | | -2(6-10n)2=10(2n-6) | | 5(3x+8)=5 | | -9(f-6)= | | 64m^19= | | 5k+1+2k=-20 | | 9x+4=-10 | | -5-6y+6=10 | | 10(3e-7)= | | 7y+3=-(3y+5)-2 |